Impoliteness and Gender Differences in the Edge of Seventeen Movie (Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
This paper aims to analyze the impoliteness strategies performed by the main female character (Nadine) and her male interlocutors in the Edge of Seventeen movie. Taking Nadine’s impolite utterances and her male interlocutors as the data, this study found a thought-provoking fact that women who have been stereotyped as “powerless” language users also have the potential to use impoliteness strategies as a way of negotiating and constructing their identity. While both genders could use impoliteness strategies to negotiate and construct their power and identity in interactions, there were differences in the use of the strategies. Women prefer to use positive impoliteness while men use negative impoliteness strategies. The use of positive impoliteness among women is influenced by their empathetic nature to social relations. Any sensitive topic to social relations is considered effective as a face-threatening act. On the other hand, men use negative impoliteness to force their interlocutors to submit to their will, a trait of male dominance. By suppressing the freedom of choice of the interlocutor, the negative face is threatened. From these findings, it can be concluded that impoliteness can be used, by men and women, as a tool to exercise their power and construct their gender identity.